Explaining power and authority in international courts. (September 2021) - Capps, Patrick; Olsen, Henrik Palmer
Abstract: It has recently been suggested that the study of international legal life should take an 'empirical turn': a turn which has often focused on how patterns of authority emerge and operate in relation to international courts. In what follows it is argued that this empiricism fails to distinguish (for the purposes of sociological inquiry) authority from various other concepts such as power or consensus in the study of international law and courts. This is because this method focuses only on overt signs, such as observable action or statements of intention, and at the level of the sign these concepts are not obviously distinguishable. However, one solution to this problem, which is to collapse socially significant and distinct categories such as authority and consensus into a broad category of 'power', requires the adoption of an implausible and inconsistent view of agency in explanations of legal authority. By contrast, and in line with the long-standing interpretivist tradition in sociological and legal method, we claim that in order to interpret the observable signs of compliance to international legal rules and principles as indicative of authority, consensus, or power, it is necessary to interpolate an account of the reasons which give rise to the compliance we observe. This, in turn, explains why international legal doctrine, as an axiological structure, gives rise to the behaviour of its addressees, such as state officials.